FROZEN FOOD OLAHAN SINGKONG: ALTERNATIF SOLUSI KETAHANAN PANGAN KELUARGA DI KAMPUNG ANAKA KOTA TASIKMALAYA - Edy Suroso; Dedi Rudiana; Allicia Deana Santosa; Aquinaldo Sistanto Putra; Agis Andriani (Bajang Institute, 2022)
The Enforcement of Restrictions on Emergency Community Activities (PPKM ) implemented by the government in an effort to overcome the Covid-19 Pandemic has a direct impact on various orders of community life, especially causing a family food security crisis. This is also felt by most of the residents of Anaka Village, Urug Village, Kawalu District, Tasikmalaya City. Kawalu District is the area with the largest cassava production capacity in Tasikmalaya City. Kampung Anaka is one of the centers for cassava production. So far, cassava is only used by selling it directly as a commodity or some of it is consumed in the traditional way, namely steamed or fried. This community service program (PPM) aims to provide knowledge to housewives about entrepreneurship for family economic resilience through the frozen food business. In addition, workshops on making cassava chicken nuggets are also provided. The output of this PPM activity is the formation of a productive economic business group (KUEP) called